HEGEMONI LABA AKUNTANSI DALAM ETIKA BISNIS (KRITIK ANTONIO GRAMSCI) - Nurdina; R. Yudi Sidharta (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This article uses Antonio Gramsci's hegemonic thinking to critically examine accounting earnings within the framework of business ethics. In the realm of accounting, critical scientists offer a new view as an alternative that can radically replace various current modes of accounting practice, especially aspects of injustice that are generated or supported by accounting. The practical view sees business as a purely profit making activity, even if profit is considered the sole main purpose of business. Currently there are concerns from many parties in Indonesia that the phenomenon of unethical business methods will develop. There is even an assumption that unethical business practices are legal, if you want to gain the maximum profit or profit according to economic principles. This paper aims to arouse our awareness that business success is not only determined by company profits and growth. The perpetuation of capitalist domination in accounting is supported by traditional intellectuals who use their hegemony in spreading these capitalist values.Therefore, counter-hegemony is needed as mentioned by Gramsci, namely organic intellectuals to free the people from the domination of hegemony of capitalism.